(3eNJUQ GdEHGfI Yf TQjYI GdaQbI GdfGLjI heLGfHI GdaQb GdePeheIs - (3GdYcHQj GdMfHdj, CHh YHO Gddg GdeYQha HGHf HWI, YHjOGddg Hf eMeO Hf eMeO Hf MeOGf Hf YeQ GHf YjSi Hf EHQGgje Hf SYO Hf YJHI, J (B387(3g`s ((3YeGO Hf CHj HcQ, GdTGaYjs)
(3BNQgG (B:s
(3aj BNQg Cfg JeJ ebGHdJg Ydi CUdg HJGQjN (B: 20 (3Pj GdMLI (B719(3g` Ydi jO(B: (3CMeO Hf Ydj Hf CHj HcQs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc d`(B: (3CMeO Hf Ydj Hf CHj HcQs
Keywords: (3GdMOjK hGdeUWdMs